English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

2006-12-12 20:17:14 · 4 answers · asked by agus s 1 in Science & Mathematics Mathematics

4 answers

Integral (1/(1-x)^2) dx

This one is actually fairly simple, because something linear is being squared. Note that 1/(1 - x)^2 is equal to (1 - x)^(-2).

Integral ( (1 - x)^(-2) )dx

We can use simple substitution to solve this.

Let u = 1 - x
du = (-1) dx
(-1) du = dx

And we substitute, to get

Integral (u^(-2) (-1)du)

Pulling out the constant -1, we get

(-1) * Integral (u^(-2))du

Which we can use the reverse power rule for.

(-1) [u^(-1) / (-1) ] + C

or

u^(-1) + C

or

1/u + C

and now we replace u = 1 - x, to get

1/(1 - x) + C

2006-12-12 20:23:43 · answer #1 · answered by Puggy 7 · 0 0

notes:y=1-x then dy=-dx and the integral is -1/y^2dy=1/y for y=1-x then we find the integral : 1/(1-x)

2006-12-13 04:24:32 · answer #2 · answered by grassu a 3 · 0 0

1-x=t dx=-dt
1/(1-x)^2dx=-1/t^2
==1/t==1/(1-x) +c

2006-12-13 04:25:56 · answer #3 · answered by Far 1 · 0 0

int 1/(1-x)^2 dx=int (1-x)^-2dx= 1/3*(1-x)^-3]+c

2006-12-13 05:09:40 · answer #4 · answered by J.Bo 2 · 0 0

fedest.com, questions and answers